EFFECTIVENESS OF A STRUCTURED PSYCHIATRIC COUNSELLING INTERVENTION ON PSYCHOLOGICAL DISTRESS AND CAREGIVER FATIGUE AMONG PEDIATRIC ONCOLOGY CAREGIVERS - Wani, Sadaf Shafi; Guru, Faisal Rashid; Amin, Noorul (Universitas Airlangga, 2026)
Introduction: Caregivers of pediatric oncology patients play a crucial role in treatment adherence and emotional support, but often face significant psychological distress and physical fatigue, affecting their well-being and caregiving. This study assessed the impact of structured counseling on reducing distress and fatigue among these caregivers in a tertiary care setting. Methods: A pre–post interventional study involved 50 caregivers, measuring psychological distress with the Distress Thermometer and fatigue using the SAFE Scale. Baseline assessments were conducted prior to four individualized counseling sessions aimed at providing support, developing coping strategies, managing stress, and encouraging self-care. Post-intervention assessments utilized the same tools to evaluate changes in distress and fatigue. Results: Following the counseling intervention, caregivers exhibited statistically significant improvements across all measured outcomes. Mean distress scores decreased from 8.92 ± 0.80 to 4.96 ± 0.86, reflecting a mean reduction of 3.96 points (p < 0.001). The mean extent of fatigue declined from 15.00 ± 0.00 to 4.38 ± 0.49, indicating a mean reduction of 10.62 points (p < 0.001). Similarly, the mean fatigue impact score fell from 30.00 ± 0.00 to 12.00 ± 0.00, with a mean reduction of 18.00 points (p < 0.001). Conclusion: Structured psychiatric counseling significantly alleviated psychological distress and physical fatigue among caregivers of pediatric oncology patients. Integrating caregiver-focused counseling into routine pediatric oncology care may enhance caregivers' well-being and, in turn, improve patient outcomes.